ConciliaMed: an interactive mobile and web tool to reconcile chronic medications of patients undergoing elective surgery - Bernardo Santos-Ramos; Eva Rocío Alfaro-Lara; María Dolores Santos-Rubio; Pablo Ciudad-Gutiérrez; Paloma Suárez-Casillas; Ana Belén Guisado-Gil (BMJ Health & Care Informatics)
Objective The last decade has seen exponential growth in electronic health tools. However, only a limited number of electronic medication reconciliation tools have been developed and implemented in healthcare settings. Here, we present ConciliaMed, a mobile and web-based tool for healthcare professionals to reconcile the chronic medications of patients undergoing elective surgery.Methods A research team of pharmacists and internists worked together with a technology company to design and develop ConciliaMed. Evidence-based guidelines were collected for inclusion in the tool. A group of experts conducted a simulation with a preliminary version of ConciliaMed to identify bugs and technical improvements and to assess their satisfaction with the application. The final prototype of the tool was disseminated through clinical meetings and the Google Store.Results Four easy-to-use and interactive modules can be used to reconcile chronic medications through the app, while the web platform is designed for consultation and learning. A higher level of satisfaction with the tool was achieved by the test participants (4.67±0.58). The triggering of dose and duplication alerts for users or the integration of ConciliaMed with electronic prescription systems were some of the more requested adaptations by the test participants.Discussion The ability to generate an editable reconciliation report or transfer information between users are some of the features of ConciliaMed that encourage its use. The integration of ConciliaMed into the healthcare workflow is expected.Conclusion The web platform is freely available online (https://conciliamed.chronic-pharma.com), as is the mobile application through the Google Store, making it easily accessible to healthcare professionals.